The consumer psychology of brands - Schmitt, Bernd (Journal of Consumer Psychology, 2012)
AbstractThis article presents a consumer‐psychology model of brands that integrates empirical studies and individual constructs (such as brand categorization, brand affect, brand personality, brand symbolism and brand attachment, among others) into a comprehensive framework. The model distinguishes three levels of consumer engagement (object‐centered, self‐centered and social) and five processes (identifying, experiencing, integrating, signifying and connecting). Pertinent psychological constructs and empirical findings are presented for the constructs within each process. The article concludes with research ideas to test the model using both standard and consumer‐neuroscience methods.